Effects of boron modifications on phase nucleation and dissolution temperatures and mechanical properties in 9%Cr steels: alloy design. (26th February 2020) - Akhtar, Modassir; Khajuria, Akhil; Pandey, Manish Kumar; Ahmed, Iqbal; Bedi, Raman
Abstract: This paper was dedicated to rationalizing the effect of boron modifications in alloy design of 9%Cr steels. It acquired the values of nucleation and dissolution temperatures, and mechanical properties (further referred to as properties) from computational software. Subsequently, properties were validated for five different boron modifications and were used to analytically model the behavior of boron with their computationally evaluated values. Different mathematical functions were designated for phases/properties. All phases revealed decay behavior except borides, which depicted growth behavior and no relationship for V(N, C)/Nb(C, N)/MB. Whereas, properties exhibited growth behavior, except for linear elongation and strain hardening coefficient. Besides, some phases/properties showed piecewise behavior. For an in-depth understanding of the effects of boron modifications, saddle point(s) and zone of saturation(s) were determined. A decrease in nitrogen contents as per ASTM recommendations to ppm level was found effective to increase boron concentration. This combination avoided BN and concurrently improved properties. Boron in small amounts was found effective due to the decreasing nature of multiplication factors of analytical models. Half value as a design parameter was selected. For phase and property considerations, it was 346–468 ppm and 204–239 ppm, respectively. Due to the scope of improving properties, the gradient-based optimization approach was adopted, and the upper design limit of boron was fixed as 350 ppm.